Clinical presentations and prognosis of metformin-associated lactic acidosis patients in the intensive care unit: A 20-year survey. Issue 27 (8th July 2022) - Yang, Chun-Chieh; Weng, Shih-Feng; Tseng, Kuei-Ling; Ho, Chung-Han
Abstract : Metformin-associated lactic acidosis (MALA) is a rare but serious adverse event. It is associated with a high mortality rate and is diagnosed by the peak lactate level (PLL). This study examines the relationship between the clinical presentations and PLL in patients under metformin therapy admitted to the intensive care unit (ICU) to better diagnose MALA and prevent a worsening prognosis. The mortality distribution of clinical characteristics among patients with MALA was also examined. Methods: We retrospectively analyzed 82 adult patients with MALA admitted to the ICU over 20 years. The association between the clinical parameters and mortality post-MALA was estimated using logistic regression analysis. Results: Patients with MALA admitted to the ICU presented with clinical symptoms mainly associated with the head (40.24%), chest (41.46%), and abdomen (35.37%). Additionally, the PLL distribution significantly varied with age, APACHE II = Acute Physiology and Chronic Health Evaluation II (APACHE II) score, various laboratory parameters like nadir arterial bicarbonate level, multiple treatment modalities such as renal replacement therapy, and mortality. The overall mortality rate was 17.07%. After adjustment of age and gender, the significant predictors of mortality were APACHE II score, PLL, vasoactive support, ventilator support, and cardiopulmonary resuscitation. Conclusions: Despite MALA being a rare event, it is necessary to evaluate its clinical characteristics, especially the associated PLL and mortality. In the current study, higher levels of APACHE II score and PLL show a greater likelihood of mortality in MALA patients.